Numerical Analysis of Arterial Plaque Thickness and its Impact on Artery Wall Compliance - Vallez, LJ; Sun, B; Plourde, BD; Abraham, JP; Staniloae, CS (Journal of Cardiovascular Medicine and Cardiology, 2015)
A numerical analysis was completed on the influence of plaque on the compliance of an artery wall. The analysis allowed a systematic variation of the transluminal pressure difference and plaque thickness. Included in the analysis was a sheath of surrounding tissue that provides support during the cyclical deformation. The analysis incorporated progressively thicker layers of plaque to quantify their impact on the artery compliance. It was found that the presence of plaque plays a significant role in reducing the compliance. It is also shown that modest reductions in plaque thickness can result in large changes in the compliance and a positive health outcome. The calculations also included only a health artery (absence of plaque). The healthy artery possessed the largest compliance of the cases. The healthy-artery results were compared with literature and found to be in good agreement. The calculations were made with four different transmural pressure variations to capture the entire range of possible values. The results for all pressure waveforms agreed qualitatively although there was some difference in magnitude.